2022
DOI: 10.3389/fnins.2022.808776
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Psychosocial Determinants Underlying the Onset and Maintenance of Alcohol Use Disorder

Abstract: A large number of different mechanisms have been linked to Alcohol Use Disorder (AUD), including psychosocial, neurocognitive, affective, and neurobiological factors. Gender has been shown to impact the presentation and progression of AUD; yet, little work has been done to parse the different mechanisms underlying AUD within the lens of gender differences. A review of the literature on adolescence revealed that psychosocial factors, in particular lack of family social support and interactions with peers, drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
5
14
0
Order By: Relevance
“…Spechler and colleagues (2019) found that individual level factors such as sensation/novelty seeking were predictive of cannabis use onset in boys, whereas factors that are more closely linked to the environment, such as verbal IQ, sexual relationships and parent personality, were predictive in girls 10 . These findings also fit with our recent review and empirical data demonstrating a much greater importance of social support as a protective factor preventing the escalation of alcohol use in adolescence and maintenance of alcohol misuse in adulthood particularly in girls and women, as compared to boys and men 101 . We are only aware of one previous study on sex/gender differences in CUD in adults 102 .…”
Section: Discussionsupporting
confidence: 90%
“…Spechler and colleagues (2019) found that individual level factors such as sensation/novelty seeking were predictive of cannabis use onset in boys, whereas factors that are more closely linked to the environment, such as verbal IQ, sexual relationships and parent personality, were predictive in girls 10 . These findings also fit with our recent review and empirical data demonstrating a much greater importance of social support as a protective factor preventing the escalation of alcohol use in adolescence and maintenance of alcohol misuse in adulthood particularly in girls and women, as compared to boys and men 101 . We are only aware of one previous study on sex/gender differences in CUD in adults 102 .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, recovery was a subjective report indicating the age they last experienced AUDrelated symptoms. As females did not seek help for their AUD, formal treatments such as pharmacotherapy and psychotherapy were not reasons for their symptom alleviation and recovery (Holzhauer et al, 2020;Maxwell et al, 2022;Tucker et al, 2020). Pregnancy and motherhood and the responsibilities associated with it could explain the earlier age of recovery in females in this study, but not completely (Nolen-Hoeksema, 2004;Nolen-Hoeksema & Hilt, 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Tucker et al (2020) reported that approximately 70% of individuals with AUD and maladaptive drinking patterns experience natural recovery, where they see an improvement without formal interventions. In another study, Maxwell et al (2022) reported that social support for women, but not in men, plays a greater role in regulating alcohol use. They found that increased social support helped build a barrier against negative affect, mental health symptoms, and poor self-regulation which alleviates AUD severity (Maxwell et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One study reported that men have a higher rate of accessing healthcare prior to being diagnosed with alcohol-related LC than women, but they are less likely to receive interventions or referrals than women (57). Nevertheless, women report having less social support for treatment engagement when dealing with alcohol use disorders (58). To formulate effective and accessible prevention and treatment options, these factors should be taken into account.…”
Section: Discussionmentioning
confidence: 99%